Psychometric Properties of the Abdominal Pain Index (API) in the Iranian Adolescent Population - Sepideh Hoseini; Mahdi Jafari; Zahra Asl Soleimani; Kaveh Qaderi Bagajan; Meysam Sadeghi; Shadi Zolfaghari (Pain Research and Management)
Considering the high prevalence of abdominal pain in children and adolescents in Iran, it is essential to use appropriate screening tools. One of the most comprehensive, yet concise, tools for this purpose is the Abdominal Pain Index (API). This study aimed to investigate the psychometric properties of the Persian version of the self-report API in adolescents. In this descriptive study, A total of 162 Iranian adolescents in the age range of 12 to 18 years were considered as the sample group, which included two groups of school students (n = 125) and adolescent patients with abdominal pain (n = 37). Clinical sample was selected by the available sampling method, and nonclinical sample was selected by the cluster sampling method. Adolescents in the sample group were selected from both clinical and nonclinical groups in order to evaluate differential validity. Instruments, including API, somatic symptoms subscale of the General Health Questionnaire (GHQ), and McGill Pain Questionnaire (MPQ), were also completed for the participants. Also, to evaluate the construct validity of API, exploratory and confirmatory factor analysis methods were applied. The exploratory factor analysis identified one general factor, and the confirmatory factor analysis results show the model’s satisfactory fitting. Also, the researchers’ hypothesis, i.e., API is a single-factor model (with five items), was approved. The reliability coefficient of the questionnaire was satisfactory for the total scale (α < 0.7). This study showed that API could be used with considerable confidence for Iranian children and adolescents with chronic pain.